PRIDENA: Its Contribution to Social Research on Childhoods and Adolescences in Costa Rica - Fernández Aguilar, Rolando (2025)
Introduction: In a political, social and economic context that violates the rights of children and adolescents, it is necessary to define lines of research and action in this matter. The article analyzes the trajectory and contributions of the Interdisciplinary Projects of Studies and Social Action on the Rights of Children and Adolescents (PRIDENA-UCR) to research and social action aimed at children and adolescents, between the period 2004-2024. Objective: The objective is to reconstruct PRIDENA's contributions to research on children's and adolescents' rights and to define research lines that respond to the sociopolitical context. Method: An exploratory and descriptive qualitative methodology was employed, including literature review, document analysis, and in-depth interviews with key PRIDENA stakeholders. Additionally, technique triangulation was used to analyze the context and empirical findings. Results: Three main areas were identified: PRIDENA's historical trajectory, its role in research and social action, and strategic research lines. These include the evaluation of protection and autonomy paradigms, public policy analysis, children’s and adolescents' participation, and studies on violence and exclusion. [Continue reading in article]